Konsep dan model penyusunan tipologi pesisir Indonesia menggunakan teknologi sistem informasi geografi - Suprajaka,; Aris Poniman,; Hartono, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2005)
This paper describes a study on the lineaments of Indonesia’s coastal typological mapping at the detail national scale of 1:2500000. In line with the national scope of the mapping, this study focuses on the results of analytical interpretation of available data sources, namely, geological maps which were utilized as a basis for analyzing the abiotic aspects, in particular, in determining the material of the coastal areas. The biotic aspects are further ordered according to vegetation maps, while the cultural aspects (socio-economic)are the results of data interpretation which might reflect the natural and the cultural factors involved. Results of the interpreted data are then validated using remotely sensed data available, in particular, the LANDSAT data including the MSS and the TM which cover several locations including those of the Marine Resource Evaluation and Planning (MREP) Project pertaining to 10 Marine and Coastal Management Area(MCMA)provinces.Overall, the Indonesian coastal typology is dominated by the muddy coastal mangrove ecosystem which has been inhabited for as far as 10,654 km or 16.45% of the area observed; while the least typology comprises rocky coastal forest ecosystem which habitation spans 1,106km or 1.71% of the area observed